(untitled) (Research, Society and Development, 2021)
Depression and sleep disorders are frequent in patients with HIV. The aim of this article is to detect sleep disorders and depression related to antiretroviral therapy in the adult population with HIV/AIDS. The following scales were applied: Patient Health Questionnaire-9 (PHQ-9), Epworth Sleepiness Scale, adapted to Brazil (ESS-Br), and the Pittsburgh Sleep Quality Index Questionnaire (PSQI). CEP: 3.319.628. In the sleep assessment (PSQI), use of Dolutegravir (DTG) showed 58.8% poor sleep quality, Efavirenz (EFZ) was 38% indicative of poor sleep and 28.5% of sleep disorder, and Atazanavir-ritonavir (ATV-r) with poor quality sleep was found in 40%. The detection of any type of sleep disorder did not differ statistically between the use of EFZ or DTG (p = 0.79). Regarding the assessment of ESS-Br sleepiness, we detected 4.7%, 17.2% and 20% important alterations in patients using EFZ, DTG and ATV, respectively. The analysis obtained for depression (PHQ-9) was moderately severe (EFZ = 10%, DTG = 20.3%, ATV = 0%) and severe (EFZ = 15%, DTG = 6.2%, ATV = 0%). This study showed that HIV-positive individuals suffer from sleep disturbances independent of the ART regimen, but with greater impact with Efavirenz. Daytime sleepiness was present in one in every 5 individuals using ART. And the greater severity of depression was found to be important for the groups using Efavirenz and Dolutegravir.